2016
DOI: 10.1098/rstb.2015.0070
|View full text |Cite
|
Sign up to set email alerts
|

Psychological autonomy and hierarchical relatedness as organizers of developmental pathways

Abstract: One contribution of 16 to a theme issue 'Understanding self and other: from origins to disorders'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 38 publications
2
48
1
16
Order By: Relevance
“…In terms of the home environment, they found that mothers provided greater autonomy support (i.e., supporting the child’s self-governance and control over their life; Keller, 2016) compared to fathers prior to the transition. Moreover, Duineveld et al (2017) reported greater levels of autonomy support before the transition significantly predicted a decline in depression after children moved to secondary education.…”
Section: The Effects Of the Transition To Secondary Education On Emotmentioning
confidence: 99%
“…In terms of the home environment, they found that mothers provided greater autonomy support (i.e., supporting the child’s self-governance and control over their life; Keller, 2016) compared to fathers prior to the transition. Moreover, Duineveld et al (2017) reported greater levels of autonomy support before the transition significantly predicted a decline in depression after children moved to secondary education.…”
Section: The Effects Of the Transition To Secondary Education On Emotmentioning
confidence: 99%
“…In this issue, the paper by Keller [24] lays this point out in compelling detail. Children, socialized into societies with a high appreciation of relatedness, instil in their children an urgency of sharing with others in ways in which societies with a strong emphasis on autonomy will not.…”
Section: Prosocialitymentioning
confidence: 99%
“…The papers contributed by Heyes [22], Schmelz & Call [23] and Keller [24] as a collective, demonstrate the inordinate value accrued to attempts at understanding the evolution of the human mind by collating research endeavours from developmental, comparative and cross-cultural psychology. Our aim here is to build on this triadic approach, to argue for its value and to provide insight into some of the key elements that make us who we are: social learning, cooperation, prosociality and understanding of other minds.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudiosos do tema entendem que os objetivos dos pais em relação ao processo de socialização dos filhos a médio e longo prazos, bem como suas avaliações do comportamento infantil, são influenciados culturalmente (Otto & Keller, 2016;Tamm, Kasearu, Tulviste, & Trommsdorff, 2016). Assim é que, no que concerne às necessidades humanas de autonomia e relação interpessoal (Kağitçibaşi, 2007), há culturas em que os pais tendem a desejar que seus filhos atinjam elevado grau de autonomia, enquanto em outras, predominam metas de desenvolvimento marcadas pela forte interdependência e ligação ao grupo social e aos demais indivíduos que o constituem (Keller, 2016;Keller & Kärtner, 2013). Um sistema de crenças parentais mais individualista, de acordo com Leyendecker et al (2002), se relaciona a uma valorização maior da independência e autonomia na criança, refletida, no estudo que empreenderam, em uma maior frequência de respostas nas categorias definidas pelos autores como autoaperfeiçoamento e autocontrole.…”
Section: Introductionunclassified